Safety interlock and vent system to alleviate potentially dangerous ice blockage of top‐loading cryostat sample sticks. (23rd June 2013) - Pangelis, S.; Olsen, S. R.; Scherschligt, J.; Leão, J. B.; Pullen, S. A.; Dender, D.; Hester, J. R.; Imperia, P.
<x xml:space="preserve">Abstract</x> A combined solution is presented for minimizing the safety hazards associated with closed cycle cryostats described by Swainson & Cranswick [J. Appl. Cryst. (2010), 43, 206–210]. The initial solution is to install a vent tube with one open end deep inside the sample space and a pressure relief valve at the top. This solution works for either a cryogen or a cryogen‐free (closed cycle) system. The second approach, which can be combined with the first and is applicable to cryogen‐free cryostats, involves electrically interlocking the closed cycle refrigerator compressor to the sample space, so that the system cannot be cooled in the presence of a leak path to air.